Fibrin Glue Increases the Tensile Strength of Conduit-Assisted Primary Digital Nerve Repair. (January 2018) - Childe, Jessica R.; Regal, Steven; Schimoler, Patrick; Kharlamov, Alexander; Miller, Mark C.; Tang, Peter
Background: An ideal peripheral nerve repair construct does not currently exist. Our primary goal was to determine whether fibrin glue adds to the tensile strength of conduit-assisted primary digital nerve repairs. Our secondary goal was to evaluate the impact of varying suture number and location on the tensile strength.Methods: Ninety cadaveric digital nerves were harvested and divided equally into the following repair groups: A (4/4), B (2/2), C (0/2), D (0/1), and E (0/0) with the first number referring to the number of sutures at the coaptation and the second number referring to the number of sutures at each proximal and distal end of the nerve-conduit junction. When fibrin glue was added, the group was labeled prime. The nerve specimens were transected and then repaired with 8-0 nylon suture and conduit. The tensile strength of the repairs was tested, and maximum failure load was determined. The results were analyzed with a 2-way analysis of variance. The Tukey post hoc test compared repair groups if the 2-way analysis of variance showed significance.Results: Both suture group and glue presence significantly affected the maximum failure load. Increasing the number of sutures increased the maximum failure load, and the presence of fibrin glue also increased the failure load.Conclusions: Fibrin glue was found to increase the strength of conduit-assisted primary digital nerve repairs. Furthermore, the number of sutures correlated to the strength of the repair. Fibrin glue may be added to a conduit-assisted primary digital nerve repair to maintain strength and allow fewer sutures at the primary coaptation site.